2023
DOI: 10.3390/su15032283
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Social Media for Development Communication and Social Change: A Review

Abstract: The use of social media to share knowledge is interesting and in demand by many people. Literature studies on the use of social media to share knowledge have been widely carried out, but studies on development communication and social change need further exploration. This study aims to provide a review of research on the use of social media for knowledge sharing in the context of development communication and social change. This research is a systematic literature review using the PRISMA protocol. This protoco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 118 publications
0
9
0
1
Order By: Relevance
“…This research found that the factors that shape this behavior are the adequacy of knowledge and confidence and the farmers' enthusiasm for carrying out robusta coffee red-picking practices. This research focuses on farmers' knowledge-sharing behavior and media use to share knowledge, with less emphasis on the knowledge-sharing process, considering that this area needs to be further explored (Ihsaniyati et al, 2023). Farmers' knowledge-sharing activities shape their knowledge, enthusiasm, and confidence in red-picking.…”
Section: Knowledge-sharing Behavior and Practice Of Robusta Coffee Re...mentioning
confidence: 99%
See 2 more Smart Citations
“…This research found that the factors that shape this behavior are the adequacy of knowledge and confidence and the farmers' enthusiasm for carrying out robusta coffee red-picking practices. This research focuses on farmers' knowledge-sharing behavior and media use to share knowledge, with less emphasis on the knowledge-sharing process, considering that this area needs to be further explored (Ihsaniyati et al, 2023). Farmers' knowledge-sharing activities shape their knowledge, enthusiasm, and confidence in red-picking.…”
Section: Knowledge-sharing Behavior and Practice Of Robusta Coffee Re...mentioning
confidence: 99%
“…Research on practicing social media to share knowledge has been widely conducted. Ihsaniyati et al (2023) examined 57 highly reputable articles using the PRISMA protocol. Similar studies have previously presented definitions of social media use for knowledge sharing.…”
Section: Knowledge-sharing Behavior Based On Access To Social Mediamentioning
confidence: 99%
See 1 more Smart Citation
“…These communities, which may be based on interests, industries, or professions, provide a forum for individuals to share information, insights, and best practices. By participating in these communities, individuals can learn from one another, acquire new skills, and stay abreast of the most recent trends and developments in their field [11,12]. There are, of course, challenges associated with the use of social media for knowledge transfer.…”
Section: The Benefits Of Social Media For Knowledge Transfermentioning
confidence: 99%
“…Knowledge sharing by coffee farmers will expand the range of dissemination, knowledge, and enthusiasm in implementing quality standards. Previous studies stated that farmers and the agricultural sector still have a small portion of knowledge sharing research [10].…”
Section: Introductionmentioning
confidence: 99%